Examining Bicycle Safety on a College Campus: Observations and Rationale for Unsafe Cycling. (September 2014) - Lavetti, Eric; McComb, Sara
Riding a bicycle is a popular, environmentally friendly, and cost effective alternative to automobiles as a method of transportation as well as an activity for recreation and fitness. An important aspect of bicycle safety includes why cyclists ride in unsafe ways. Observations were conducted to establish a baseline rate in which cyclists committed violations. The research determined that violations do indeed occur and at a very high frequency. After the baseline was established, interviews were conducted to better understand what factors contributed to unsafe cycling behavior. The results indicate several specific reasons the observed violations occur. Further research is needed to determine cyclists' rationale for unsafe cycling behaviors that could put them at risk.